Evaluation of patient education materials for stereotactic radiosurgery from high-performing neurosurgery hospitals and professional societies. Issue 1 (3rd July 2019) - Rooney, Michael K; Golden, Daniel W; Byun, John; Lukas, Rimas V; Sonabend, Adam M; Lesniak, Maciej S; Sachdev, Sean
Abstract: Background: Little is known about the readability and utility of patient education materials for stereotactic radiosurgery (SRS). Therefore, the goal of this investigation was to evaluate such materials from high-performing neurosurgery hospitals and professional societies through an analysis of readability and educational content. Methods: In this cross-cross sectional study, 61 websites associated with the top 50 neurosurgery and neurology hospitals according to U.S. News & World Report (USNWR) and 11 predetermined professional medical societies were queried. Identified SRS education materials were analyzed by 6 readability indices. Educational content was assessed by 10 criteria based on surveys of patients' perspectives about SRS. Results: Fifty-four materials were identified from the target population (45 from USNWR hospital websites and 9 from professional society websites). Mean readability of materials ranged from 11.7 to 15.3 grade level, far more difficult than national recommendations of sixth and eighth grade. Materials were found to have deficiencies in educational content. Compared with high-performing hospitals, materials from websites of professional societies were longer ( P = .002), and more likely to discuss risks and benefits specific to SRS ( P = .008), alternative treatment options ( P = .05) and expected outcomes or postprocedure descriptions ( P = .004). Hospital materials were also more likely to favor brand-specific terminology (eg, GammaKnife) over generic terminology (eg, radiosurgery; P = .019). Conclusion: Publicly available online patient educational materials for SRS are written at reading levels above national recommendations. Furthermore, many lack information identified as important by patients. Reevaluation and improvement of online SRS educational materials on a national scale are warranted.